CoCoNutTrix: A Study in Collaborative Retrofitting for Information Visualization - Isenberg, Petra; Bezerianos, Anastasia; Henry Riche, Nathalie; Carpendale, Sheelagh; Fekete, Jean-Daniel (Special Issue on Collaborative Infovis, IEEE Computer Graphics and Applications Journal, 2009)
Most information visualization systems incorporate little or no specific support for collaboration. Yet, collaboration has been identi- fied as a means to deal with the increasing amount and complexity of information available to analysts. Re-implementing existing applications to fully incorporate our current understanding of computer supported cooperative work could be exhaustive, time consuming, and expensive. As a first step, we explored how co-located collaborative information visualization and analysis environments can be created in a cost-effective manner. We retrofitted NodeTrix, a social network analysis tool, by extending it to enable multi-user interaction in collaborative environments. We present details of the retrofitting process and results of a user study assessing the usability of our retrofitted system. Our results support the effectiveness of our low-cost collaborative retrofitting for collaborative network analysis and highlight implications for practitioners.